Psychrophilic anaerobic digestion of swine manure slurry in intermittently fed sequencing batch reactor. - Masse, Daniel I. (University of Ottawa (Canada), 1995)
Animal manure management practices, principally in regions where there is a surplus of manure are often detrimental to the environment and also represent a potential hazard to human and animal health. The primary objective of this study was to evaluate the feasibility of psychrophilic anaerobic digestion (PAD) in sequencing batch reactors (SBR) as a low cost and easy to operate process to: (a) reduce the pollution potential of swine manure slurry; (b) recover energy; and (c) reduce odours of swine manure slurry. Experiments were carried out in 12 40-Litre SBRs operated under different conditions. Experimental results indicated that PAD of swine manure slurry at 20$\sp\circ$C in intermittently fed SBR: (1) reduced the pollution potential of swine manure slurry by removing 85 to 95% of the soluble chemical oxygen demand (SCOD); (2) produced biogas at rates from 0.48 to 0.66 L of CH$\sb4$ per gram of volatile solids (VS) fed; and (3) successfully reduced odours. In all experimental runs, the PAD of swine manure slurry in SBR was found very stable. Other interesting findings were that PAD in SBR process does not require mixing and can be intermittently fed only once and three times a week without affecting the SBR stability and performance. The second objective of this study was to model PAD of swine manure slurry in SBR in order to: (1) increase knowledge of PAD in SBR; and (2) predict process performance. Existing mathematical models of anaerobic digestion formed the basis for the two models proposed in this study for PAD in SBR. These two models were: (1) a simple model that considered only two populations of bacteria as well as particulate solubilization rate; and (2) an advanced model that considered six populations of bacteria as well as the interaction between the biological, liquid (physico-chemical) and gas phases. The simple model predicted reasonably well the trend in VA, SCOD accumulation as well as methane production. The advanced model which made use of a large number of kinetic constants also predicted reasonably well the methane production as well as the trend in accumulation in acetic, propionic and butyric acids, dissolved and gaseous hydrogen and SCOD.
Keywords: Environmental Sciences.